EFFECT OF ANNEALING ON THE REAL STRUCTURE AND MICROSTRUCTURE OF ADVANCED LASER PROCESSED AISI H13 TOOL STEEL - Karel Trojan; Václav Ocelík; Nikolaj Ganev; Stanislav Němeček; Jaroslav Čech; Jiří Čapek; Jakub Němeček (Acta Polytechnica CTU Proceedings)
The aim of this paper is to describe the effects of annealing on the microstructure of laser cladded AISI H13 tool steel using various methods. Advanced laser technology has the potential to replace conventional methods to make and repair dies. However, it has to be determined whether the newly created surface still needs to be heat-treated, which would cause additional repair costs. No significant effect of heat treatment on the microstructure and real structure of the clads was detected, but further confirmation, in particular by measuring wear resistance, is needed.